Under the moon : a Catwoman tale - Myracle, Lauren, 1969-; Goodhart, Isaac (Burbank, CA : DC Ink, 2019)
When living with her mother's abusive boyfriend becomes unbearable, fifteen-year-old Selina Kyle, the future Catwoman, runs away and struggles to find her own identity while living on the streets of Gotham.
Keywords: Supervillains -- Fiction; Identity -- Fiction; Runaways -- Fiction; Homeless persons -- Fiction; Graphic novels